Iron Age myth and materiality : an archaeology of Scandinavia, AD 400-1000 - Hedeager, Lotte (Routledge, 2011)
Iron Age Myth and Materiality: an Archaeology of Scandinavia AD 400-1000 considers the relationship between myth and materiality in Scandinavia from the beginning of the post-Roman era and the European Migrations around AD 400 up until the coming of Christianity around AD 1000.